2021
DOI: 10.3389/fnsys.2021.648860
|View full text |Cite
|
Sign up to set email alerts
|

How Energy Supports Our Brain to Yield Consciousness: Insights From Neuroimaging Based on the Neuroenergetics Hypothesis

Abstract: Consciousness is considered a result of specific neuronal processes and mechanisms in the brain. Various suggested neuronal mechanisms, including the information integration theory (IIT), global neuronal workspace theory (GNWS), and neuronal construction of time and space as in the context of the temporospatial theory of consciousness (TTC), have been laid forth. However, despite their focus on different neuronal mechanisms, these theories neglect the energetic-metabolic basis of the neuronal mechanisms that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 159 publications
(194 reference statements)
0
12
0
Order By: Relevance
“…Since awareness and consciousness reflect optional brain activity added with high energy costs to the basic, non-conscious signal processing, further animal studies should consider this energy aspect as an important factor of natural selection in the evolution toward possible context-dependent awareness/consciousness of a given species. A recent review ( Chen and Zhang, 2021 ) framed this new field of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since awareness and consciousness reflect optional brain activity added with high energy costs to the basic, non-conscious signal processing, further animal studies should consider this energy aspect as an important factor of natural selection in the evolution toward possible context-dependent awareness/consciousness of a given species. A recent review ( Chen and Zhang, 2021 ) framed this new field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sensorimotor and the central nervous systems need, compared to the rest of the body, high amounts of energy in order to operate adequately, there is evolutionary selective pressure on limiting energy consumption of the brain as far as feasible ( de Polavieja, 2002 ; Niven and Laughlin, 2008 ; Niven, 2016 ). For example, for producing high-frequency gamma-wave information exchange between groups of neurons in order to generate awareness and even more consciousness as explained in the first part of this review (compare Figure 2 ), the energy consumption of the brain would especially be high ( Shulman et al, 2009 ; Chen and Zhang, 2021 ). By arguments of natural selection, such a high energy consumption of the aware/conscious brain could be an evolutionary meaningful adaptation only if the individuals of a species were not affected by energy shortage in their ecological niche and/or gained a significant advantage in their own or kin reproductive fitness (e.g., West and Gardner, 2013 ) by having awareness/consciousness as a behaviorally-relevant variable.…”
Section: Awareness and Consciousness In Animals And Their Relationshi...mentioning
confidence: 99%
“…When the data from these studies were analyzed, it was found that patients with DoC had lower levels of glucose metabolism in specific regions of their brains (Arianna Sala et al, 2021). Additionally, studies have also found that when consciousness levels increase, blood glucose use roughly doubles (Hyder et al, 2013), which indicates that the level of use of blood glucose is directly related to the consciousness level and the shifts between different states of consciousness (Chen & Zhang, 2021).…”
Section: Role Of Blood Glucose Metabolism In Consciousnessmentioning
confidence: 97%
“…For the materialist camp, matter is fundamental, gives rise to consciousness, which is local (in spacetime), emergent, a product of the structure of the mechanical brain, and finite (ends at death); evidence of and for the phenomenon is grounded in the physical structure of the brain, i.e., the neural correlates of consciousness, NCC, which can be assessed and accessed via neuroscience techniques and recordings. Moreover, the fourteen parapsychological data proposed by the post-materialist camp to account for consciousness are said, from the materialist camp, to either be illusions, phenomenon generated by the neural and chemical correlates of the brain, or scientifically untestable and unverifiable (Dennett,et al [20,23,34,36,37,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)). The post-materialist camp disagrees with this materialist account and posits that the neural correlates of the brain and neuroscience techniques cannot both discount the external occurrence of consciousness, as revealed by their contrast analysis problem, and account for the subjective nature of consciousness, i.e., the hard and binding problems of consciousness, which, for post-materialists, emanates from outside of the brain (van Lommel, et al [8,9,17,18]).…”
Section: Theoretical or Conceptual Background Of The Problemmentioning
confidence: 99%